(untitled) (Herald of Journalism, 2024)
The article is devoted to the urgent topic of the short videos’ influence on the representatives of generation Z. The authors make an attempt to study the phenomenon of popularity of Shorts and Reels genres on YouTube, Instagram and TikTok. The article considers the influence of short videos on the cognitive abilities of representatives of the young generation. During the writing of the article the works of journalists and neuropsychologists on the influence of the format of storises on the younger generation in the modern media space were studied. The authors explore the phenomenon of short videos in TikTok. This platform has become a leader in the world of digital media industry. The authors try to analyse the reasons for the success of the short media format. In their opinion, the main characteristic of short videos on YouTube, TikTok, Instagram was simplicity and adaptability to the needs of modern society. The article indicates the reasons for the popularity of short media forms among generation Z. In the article the authors considered the topic of "clip thinking" among the representatives of generation Z. The aim of the research: to identify the main characteristics and differentiation between two groups: active users of digital content and consumers of mixed content (digital and print). The authors, based on the results, identified significant differences: the groups have different approaches to obtaining and assimilating information. The aim of the study is to analyse the concept of "Generation Z", to investigate the specifics of the impact of short videos on the youth audience. This format is actively used on the platforms: TikTok, YouTube, Instagram for frequent interaction of subscribers with content. The research methods are: classification, observation, questionnaire survey method, content analysis, generalisation. The scientific significance of the study lies in identifying the impact of the format of short videos on the youth audience. The authors considered it appropriate to conduct a questionnaire survey among students aged 18-22 years old, since this age group of users spends most of their time in social networks. The conclusions with recommendations are given at the end of the article. The conclusions are of a recommendatory nature and in the long term, they can help to form further vectors for digital detoxification for generation Z. Results and conclusions of the article: the format of short videos on social networks and video hosting sites should be consumed by schoolchildren and the younger generation, but in a dosed volume to avoid harmful effects on conceptual thinking.